Dermoscopy features of atypical fibroxanthoma: A multicenter study of the International Dermoscopy Society. (23rd March 2018) - Moscarella, Elvira; Piana, Simonetta; Specchio, Francesca; Kyrgidis, Athanassios; Nazzaro, Gianluca; Eliceche, Maite L; Savoia, Francesco; Bugatti, Leonardo; Filosa, Giorgio; Zalaudek, Iris; Scarfi, Federica; Inskip, Mike; et al.
Abstract: Background/Objectives: Little is known about the dermoscopic features of atypical fibroxanthoma. Methods: This was a case‐control study. Atypical fibroxanthoma lesions were compared with a control group with non‐melanoma skin cancer. Results: Altogether 40 atypical fibroxanthoma were collected. Most developed in men (93%), appearing mainly as nodular (63%), amelanotic (93%) and ulcerated (78%) lesions. Most lesions were located on the scalp (55%) and the ears (13%). Dermoscopically, most atypical fibroxanthoma displayed red (83%) and white (70%) structureless areas and irregular linear vessels (43%). A series of features achieved statistical significance when comparing atypical fibroxanthoma with non‐melanoma skin cancer. The presence of red and white structureless areas and white lines, and the absence of yellowish‐white opaque scales, hairpin vessels and arborising vessels were predictive of atypical fibroxanthoma in univariate analysis. However, when squamous cell carcinoma was excluded from the analysis, none of the criteria achieved statistical significance. When basal cell carcinoma was excluded, three variables achieved statistical significance in predicting atypical fibroxanthoma: red, structureless areas, the absence of opaque yellowish‐white scales and absence of white circles. Conclusions: Atypical fibroxanthomas seem to be barely distinguishable from basal cell carcinoma dermoscopically, but they are more easily distinguishable from a well to moderately differentiated squamous cell carcinoma. A histopathological examination is needed for the final diagnosis.